Environmental chemical risk factors for Type 2 diabetes: an update. (July 2015) - Starling, Anne P; Hoppin, Jane A
SUMMARY : Increasing evidence suggests a role for environmental chemicals in the promotion of Type 2 diabetes. This review summarizes epidemiologic studies of environmental chemical exposures reported to be associated with Type 2 diabetes and insulin resistance. Chemicals are classified as having moderate, limited and insufficient degrees of evidence in support of a diabetes-promoting effect. Moderate evidence exists for diabetogenic effects of inorganic arsenic and persistent organic pollutants, including organochlorines, dioxins and polychlorinated biphenyls. Limited evidence supports a role for environmental tobacco smoke and ambient air pollution. Insufficient evidence is available regarding the potential effects of bisphenol A, phthalates, organophosphates and pyrethroids; most studies of such short-lived pollutants have been cross-sectional and do not demonstrate causality.